Storage under pressure of dairy foods as an alternative to refrigeration - Duarte, Ricardo Valente (2022)
Hyperbaric storage (HS) at room temperature (RT) has recently sparked the scientific interest, with an increasing number of publications. HS at RT appears to be a possible alternative food preservation methodology to refrigeration (RF), with lower energy consumption and lower carbon footprint, since it is unnecessary to use energy constantly to maintain the temperature during HS, resulting also in an increase of foods shelf-life. In this work, the feasibility of HS/RT was evaluated using cow’s raw milk and cow’s and goat’s fresh cheeses and compared with storage at atmospheric pressure (AP) at RT and at RF for 60 days. It was observed that for milk, with a microbial load within the legal limits, that HS/RT allowed the preservation of raw cow’s milk, leading to a reduction in the microbial load naturally present in the milk (≥62 MPa), as well as in inoculated microorganisms, Escherichia coli, Salmonella senftenberg and Listeria innocua (≥50 MPa), and Bacillus subtilis endospores, with the fastest reductions being observed under 75 and 100 MPa. In a second set of experiments with raw milk, with a microbial load above the legal limits, HS/RT resulted in a gradual reduction of its microbial load (≥75 MPa), as well as in a greater stability after HS, when the milk stored previously at HS/RT was then subsequently placed at AP/RF. HS/RT of milk also allowed to maintain the quality of the studied parameters, such as physicochemical, enzymatic, rheological, lipid oxidation, total protein, fatty acids, and volatile organic compounds profile, similar to the ones prior storage, outperforming AP/RF for considerably longer storage periods. However, in HS/RT samples, a higher proteolytic activity may have occurred during storage, resulting in an increase in soluble protein and free amino acids after 60 days of storage. For the two types of fresh cheeses (made with pasteurized cow’s or goat’s milk) stored under HS/RT, a reduction in the microbial load during storage was observed, especially under 75 and 100 MPa. Once again, most of the physicochemical parameters were maintained throughout HS, initially being observed a compression effect of the cheeses matrix, resulting in an increase in hardness and whey loss and a decrease in the moisture content, reversing to values similar to the initial ones throughout the storage. Storage at 100 MPa/RT allowed a reduction in lipid oxidation rate, avoided the formation of undesirable volatile organic compounds and maintained better the fatty acid profile and total protein. Similarly, to raw milk, a higher proteolytic effect seemed to take place, resulting in an increase in free amino acids, especially in the longer storage periods. Despite some differences observed during HS at variable RT, it allowed the dairy products studied to be preserved for a considerably longer period (at least up to 60 days) comparatively to AP/RF, resulting in a possible extended shelf-life and microbial safety of these products.